Deux fragments d’un nécrologe de la Trinité de Fécamp (XIe-XIIe siècles). Étude et édition critique d’un document mémoriel exceptionnel - Stéphane Lecouteux (Tabularia)
The composite miscellany Paris, BnF, nouv. acq. lat. 2389 contains, on folios 33 and 34, two fragments of a necrology copied at the end of the 11th century, which was then added to throughout the following century. First noted by J.-L. Lemaitre, this little-known document has long been attributed to the abbey of Bec. However, the reconstitution of the network of confraternity of Fécamp reveals that this necrology should instead be assigned to this abbey. These fragments are of considerable interest: they belong to the oldest surviving Norman necrology and preserve the names of numerous monks linked with the abbey of Fécamp, thus demonstrating that the spiritual network established by William of Volpanio survived long after his death and those of his disciples. They also offer unparalleled evidence of the close bonds established between the abbey of Fécamp and various Benedictine monasteries in Burgundy, Normandy, Picardy, England, Lorraine, the Île-de-France and Flanders during the 11th and 12th centuries. The scriptorium of Fécamp was, at this time, at its height, and spiritual links played an essential role in the transmission of texts and the enrichment of monastic libraries.